Development of the Hepatitis E Vaccine: From Bench to Field - Zhang, Jun; Shih, James WaiKuo; Wu, Ting; Li, Shao-Wei; Xia, Ning-Shao (Seminars in Liver Disease, 2013)
Along with the improvement of diagnostic techniques, hepatitis E has attracted increasing awareness in recent years. Hepatitis E virus infection leads to high mortality in pregnant women and patients with underlying liver disease. Several hepatitis E vaccine candidates have been designed and have proved their efficacy in animal models; two candidates have successfully undergone clinical trials. Having proved safe and effective in a large phase III trials, an Escherichia coli expressed particulate protein, HEV 239, has been registered in China and is now available for use in China.
Keywords: hepatitis E virus; HEV; antigenic determinants; vaccine; immunogenicity; vaccine efficacy